2016
DOI: 10.1111/jcpp.12550
|View full text |Cite
|
Sign up to set email alerts
|

Can school counselors deliver cognitive‐behavioral treatment for social anxiety effectively? A randomized controlled trial

Abstract: With training, school counselors are effective treatment providers to adolescents with social anxiety, yielding benefits comparable to those obtained by specialized psychologists. Questions remain regarding means to maintain counselors' practice standards without external support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 37 publications
1
42
0
Order By: Relevance
“…We found 19 eligible articles representing 19 studies [13, 14, 4662] (one article reported on two different studies [55] and another two articles [51, 60] reported outcomes for the same trial). These studies represent 18 strategies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found 19 eligible articles representing 19 studies [13, 14, 4662] (one article reported on two different studies [55] and another two articles [51, 60] reported outcomes for the same trial). These studies represent 18 strategies.…”
Section: Resultsmentioning
confidence: 99%
“…This evidence base for KQ 1 consisted of 19 studies [13, 14, 4662]. Of these, one addressed KQ 2 (harms) and four addressed KQ 3 (moderators of effectiveness).…”
Section: Resultsmentioning
confidence: 99%
“…Data for the present study was collected as part of a controlled trial of Skills for Academic and Social Success (SASS), a school-based group CBT intervention for adolescent SAD [14]. The trial was approved by the Institutional Board of Research Associates at ( institution omitted ).…”
Section: Methodsmentioning
confidence: 99%
“…Adolescents were eligible for the trial if assigned a primary diagnosis of SAD. For further description of trial procedures, see Masia Warner et al [14]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation